2018
DOI: 10.1080/09575146.2018.1473344
|View full text |Cite
|
Sign up to set email alerts
|

The role of play in children’s learning: the perspective of Ghanaian early years stakeholders

Abstract: The purpose of this study was to examine Ghanaian stakeholders' beliefs about the role and importance of play in early years (3 to 5 years) children's learning, referred to as playlearning beliefs. A survey design was adopted in order to gather data necessary to examine the differences among stakeholders' play-learning beliefs. A total of 292 participants completed the survey. Data was collected using a self-developed scale. A preliminary comparison of the mean differences among the stakeholders using ANOVA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…As discussed, parental play beliefs are important in that they may impact the extent to which parents facilitate and support their children's play at home (Farver and Wimbarti, 1995;Haight et al, 1997;Avornyo and Baker, 2018;Ihmeideh, 2019). Even with increasing interest in parental play beliefs within different socio-cultural contexts (Avornyo and Baker, 2018), only a few investigations have examined the link between parents' play beliefs and their children's developmental outcomes. Lin and Yawkey (2014) found that parental play beliefs demonstrated a significant, positive relationship with their children's social competence, even after controlling for parental background variables typically associated with children's social competence.…”
Section: Present Studymentioning
confidence: 99%
“…As discussed, parental play beliefs are important in that they may impact the extent to which parents facilitate and support their children's play at home (Farver and Wimbarti, 1995;Haight et al, 1997;Avornyo and Baker, 2018;Ihmeideh, 2019). Even with increasing interest in parental play beliefs within different socio-cultural contexts (Avornyo and Baker, 2018), only a few investigations have examined the link between parents' play beliefs and their children's developmental outcomes. Lin and Yawkey (2014) found that parental play beliefs demonstrated a significant, positive relationship with their children's social competence, even after controlling for parental background variables typically associated with children's social competence.…”
Section: Present Studymentioning
confidence: 99%
“…The work led by Dr Sara Baker has resulted in a number of publications focusing on the place of executive functions and self-regulation in children's play and learning (e.g. Baker, in press;Baker & Perry, in press;Marulis, Baker, & Whitebread, 2020) as well as perspectives on play from non-Western cultures (Avornyo & Baker, 2018).…”
Section: A Brief Update On the Centre For Research On Play In Educatimentioning
confidence: 99%
“…Across diverse cultural settings, early educator differ in whether and how they perceive children's play as valuable for learning (Walsh and Fallon 2019;Rentzou et al 2019;Avornyo and Baker 2018), and in turn, their different perceptions seem to influence the approach they adopt to play as pedagogical practice Aronstam and Braund 2015). For instance, in a Canadian study , one group of early educators saw play as naturally promoting children's social development and 'foundational' skills while academic learning required direct instruction; hence, children in their classrooms spent most of their play time without adult participation; a second group ' … embraced play both as its own developmentally appropriate activity and as a pedagogical tool that had the potential to support children's learning of academic skills'.…”
Section: Studying Educator Perceptions Of Play and Learningmentioning
confidence: 99%